Fiscal stress in the U.S. states: an analysis of measures and responses - Arnett, Sarah (Georgia Institute of Technology, 2012)
Fiscal stress is an important and recurring problem that states face. Research to date on state fiscal stress involves, predominantly, cross-sectional and case study analyses and does not address the effectiveness of state responses. Many of these studies use different definitions and measures of fiscal stress compounding the difficulty of comparing fiscal stress findings. The present research effort adds to the fiscal stress literature by (1) clarifying the meaning of fiscal stress in the state context, (2) developing a measure of fiscal stress that operationalizes this meaning and is comparable across units, and 3) using this measure analyzes patterns in and the effectiveness of state responses. Fiscal stress is measured using four indexes: budget, cash, long-run, service-level. Eleven financial indicators, calculated using data from state Comprehensive Annual Financial Reports (CAFRs), are used to create these indexes for all fifty states for the years 2002-2009. Descriptive analysis compares state fiscal stress levels (grouped into low, moderate, and high fiscal stress by cluster analysis) to state economic growth rates, state responses, and institutional factors yielding several findings. First, states do not use an incremental or punctuated equilibrium strategy in responding to fiscal stress; nor do their responses follow the pattern predicted by Cutback Management theory. Second, institutional factors affect both the levels of fiscal stress and state responses to fiscal stress. Regression analysis supports and extends these findings. First, short-term responses of expenditure cuts, tax increases, and rainy day fund use do not affect state fiscal stress levels. Second, these responses have long-term effects on fiscal stress levels. A major implication of this research is that there is very little states can do in the short-term to reduce fiscal stress. However, by balancing expenditures and revenues states can set themselves up to weather the next economic downturn with lower levels of fiscal stress.